Rainfall Characteristic and Prediction in Central Maluku Using Markov Chain - Tentua, Gilldo; Waas, Valencia; Kais, Siti Djasmin; Potimau, Grace A.; Soulisa, Jihan A. S.; Wattimanela, Henry Junus (Parameter: Jurnal Matematika, Statistika dan Terapannya, 2025)
This study analyzes rainfall characteristics in Central Maluku Regency using Markov Chain methodology to model stochastic rainfall patterns. Monthly rainfall data from 2015-2024 were categorized into dry (<100 mm), normal (100-200 mm), and wet (>200 mm) conditions and processed using Microsoft Excel and R software. Results show rainfall conditions stabilize with long-term probabilities of 44.25% for wet, 32.89% for normal, and 22.87% for dry conditions. The system reaches steady state in 19 months, with 2025 predictions following this distribution. Findings support agricultural planning, disaster mitigation, and sustainable resource management in this climate-vulnerable archipelagic region.